2018
DOI: 10.1002/pssb.201800014
|View full text |Cite
|
Sign up to set email alerts
|

Valence State of Pb in Transition Metal Perovskites PbTMO3 (TM = Ti, Ni) Determined From X‐Ray Absorption Near‐Edge Spectroscopy

Abstract: We present a combined experimental and theoretical Pb-L 3 X-ray absorption near-edge spectroscopy (XANES) to investigate the chemical state of Pb in transition metal perovskites PbTMO 3 (TM ¼ Ti, Ni). A pre-edge feature originated from the excitation of a 2p core electron to the 6s orbital is only observed in PbNiO 3 , from which the valence of Pb is determined to be Pb 4þ with two 6s holes. However, no such 2p-6s related excitation was observed in PbTiO 3 , indicating the formation of Pb 2þ with fully occupie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…2b , a lower energy shoulder appeared at ~13,030 eV, which is assigned to the dipole-allowed transition from the 2 p 3/2 core level to the unoccupied 6 s state. Typically, this pre-edge can be observed in Pb 4+ ions with two 6 s holes but is absent in Pb 2+ ions with fully occupied 6 s states 49 . Therefore, we can confirm that a Pb 4+ component exists in PbFeO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…2b , a lower energy shoulder appeared at ~13,030 eV, which is assigned to the dipole-allowed transition from the 2 p 3/2 core level to the unoccupied 6 s state. Typically, this pre-edge can be observed in Pb 4+ ions with two 6 s holes but is absent in Pb 2+ ions with fully occupied 6 s states 49 . Therefore, we can confirm that a Pb 4+ component exists in PbFeO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure c, one finds that there is a sharp lower energy shoulder S d at 13,030 eV in the PFY spectrum. This lower energy pre-edge peak is assigned to the dipole allowed transition from the 2p 3/2 core level to the unoccupied 6s states, while the main peak at 13 040 eV is assigned to the transitions from the 2p 3/2 core level to the empty Pb 6d t 2 g and e g states, respectively. , It was found that the pre-edge peak S d can be observed for Pb 4+ ion with two 6s holes but is absent for Pb 2+ ion with fully occupied 6s states. Thus, the spectral intensity of the pre-edge peak S d represents the number of 6s holes and can be used to determine the valence change of Pb as a function of pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The charge disproportionation 3Cr 4+ → 2Cr 3+ + Cr 6+ has indicated a Pb 2+ valence state in Pb 2+ Cr 4+ O 3 (Cr 4+ : d 2 ). 8 Yu et al, however, claimed a Pb 2+ 0.5 Pb 4+ 0.5 Cr 3+ O 3 (Cr 3+ : d 3 ) valence state based on structural and X-ray photoelectron spectroscopy measurements. 9 However, PbFeO 3 with Fe 3+ (d 5 ) has been found to show a charge disproportionation of Pb 3+ ions into Pb 2+ and Pb 4+ in Pb 2+ 0.5 Pb 4+ 0.5 Fe 3+ O 3 .…”
Section: Introductionmentioning
confidence: 99%